2016
DOI: 10.1371/journal.pone.0163236
|View full text |Cite
|
Sign up to set email alerts
|

No Overt Deficits in Aged Tau-Deficient C57Bl/6.Mapttm1(EGFP)Kit GFP Knockin Mice

Abstract: Several mouse lines with knockout of the tau-encoding MAPT gene have been reported in the past; they received recent attention due to reports that tau reduction prevented Aβ-induced deficits in mouse models of Alzheimer’s disease. However, the effects of long-term depletion of tau in vivo remained controversial. Here, we used the tau-deficient GFP knockin line Mapttm1(EGFP)kit on a pure C57Bl/6 background and subjected a large cohort of males and females to a range of motor, memory and behavior tests and imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 29 publications
5
29
0
Order By: Relevance
“…The results were consistent with the behavior manifestations of mice in our previous experiment and Hummel’s research group’s experiment. van Hummel et al (2016), and somewhat consistent with the results described by Morris et al (2013). Thus, we considered that mere tau deficiency is not enough to contribute to the PD-like movement disorder or a decline in the number of mDANs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results were consistent with the behavior manifestations of mice in our previous experiment and Hummel’s research group’s experiment. van Hummel et al (2016), and somewhat consistent with the results described by Morris et al (2013). Thus, we considered that mere tau deficiency is not enough to contribute to the PD-like movement disorder or a decline in the number of mDANs.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we found that both young and old tau-deficient mice had no overt motor deficits in the open-field, rotarod, gait and grip strength test. These findings are in line with the findings of other research groups (Roberson et al, 2007; Ahmed et al, 2014; van Hummel et al, 2016), and partly consistent with the results of Morris’s group (Morris et al, 2013), but completely different from the reports of Lei’s group (Lei et al, 2012). …”
Section: Discussionsupporting
confidence: 88%
“…Surprisingly, mice that completely lack tau have proven to be phenotypically normal in terms of learning/memory and general cognition (13, 14, 50) with a minor motor phenotype developing later in life, the severity of which varies (1214, 56). Importantly, when endogenous murine tau is reduced in adult mice, no deviations from baseline are seen in any sensory, motor, or cognitive behavior task (15), adding support to the safety of reducing tau in the adult mammalian brain.…”
Section: Discussionmentioning
confidence: 99%
“…While further studies are clearly needed, there is evidence to suggest that inhibiting Tau-SH3 interactions would be safe. Even complete removal of Tau, which de facto would prevent all Tau-SH3 interactions, does not cause dramatic abnormalities in animals (55)(56)(57)(58)(59), and even the rather subtle changes in Tau knockout mice are not seen in Tau heterozygous mice with partial Tau reduction (19,(60)(61)(62), which better represent the incomplete block that would be provided by Tau-SH3 interaction inhibitors. In fact, Tau reduction with antisense oligonucleotides did not have apparent adverse effects in mouse models (18,63) and human clinical trials using this approach have been underway since 2017, as yet without reported adverse effects.…”
Section: Discussionmentioning
confidence: 99%